Work Engagement as A Function of Pyschological Empowerment, Self- Efficacy and Job Satisfaction among Financial Managers: A Structural Equation Modelling Approach - Flores, Joe Mari N.; Maquiling, Rebecca R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This quantitative study aimed to identify the optimal model of work engagement, focusing on psychological empowerment, self-efficacy, and job satisfaction among 400 financial managers in Davao Region, Philippines, and Daugavpils, Latvia. Employing a descriptive correlational design, data were gathered via purposive sampling and analyzed using mean analysis, t-tests, correlation analysis, regression, and structural equation modelling. Results highlighted significant levels of psychological empowerment, self-efficacy, job satisfaction, and work engagement, with psychological empowerment showing geographic variation. The study revealed strong correlations among these variables, underscoring their impact on work engagement outcomes. Amongst the five models tested, Model 5 emerged as the best fit, incorporating indicators such as psychological empowerment (meaning, competence, impact), self-efficacy (general and social), job satisfaction (remuneration, work achievement), and work engagement (physical, emotional). This model is recommended for understanding and promoting work engagement among financial managers, providing valuable insights for organizational practices to enhance employee motivation and performance.